ANALISIS PEMENUHAN HAK KONSUMEN DALAM STANDAR OPERASIONAL PROSEDUR (SOP) PT WISATA SAPTA PESONA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 - Anisa Khairunisa (2023)
Implementation of fulfilling consumer rights in Indonesia can be realized properly if business actors stipulate each company's operational rules by taking into account the legal provisions in Indonesia. This research focuses on how PT Wisata Sapta Pesona guarantees the fulfillment of consumer rights as stated in Law Number 8 of 1999 concerning Consumer Protection through company regulations in the form of Standard Operating Procedures (SOP) that apply. The research method used is normative juridical - empirical with a statutory approach and a qualitative descriptive approach; primary data in the form of Standard Operating Procedures (SOP), company survey results and company management interview results; secondary data in the form of laws and regulations, journals, books and legal articles. The results of the research show that the Standard Operating Procedures (SOP) of PT Wisata Sapta Pesona have guaranteed 6 (six) consumer rights out of 8 (eight) consumer rights regulated in Law Number 8 of 1999 concerning Consumer Protection. PT Wisata Sapta Pesona has made every effort to ensure that visitors as consumers have their rights fulfilled with several policies or programs in the form of operational audit activities. Employee training, visitor satisfaction survey and visitor reviews.